The Effect of Attachments on the Psychological Well-Being of Adolescents with Divorce Parents - Rosita, Tita (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2023)
Well-being can affect a person's mental health, this is because the positive emotions produced will make their mental condition better. The aim of this research is to determine the effect of attachment on the psychological well-being of adolescents with divorced parents. The research method used is literature study, with research subjects being teenage students with divorced parents. Based on the results of a literature review, teenagers with divorced parents tend to have low psychological well-being due to a lack of parental attachment, which causes teenagers to have insecure attachment. Insecure attachment is related to a high aspect of alienation, which is indicated by difficulty accepting oneself, difficulty accepting situations, feelings of being unwanted and unneeded, and fear of building relationships with other people. This is because they lose their main attachment figure, namely their parents. So teenagers also tend to feel sad, lonely, embarrassed, sensitive, have low self-esteem and withdraw from the environment. However, if teenagers have peer attachment, they can minimize the impact of divorce on low psychological well-being. This is because peer attachment functions as a source of psychological security for teenagers because they receive affection from their peers, apart from that it provides an experience of mutual trust and openness in communication which gives teenagers a new space to get positive affection.